Assessing hydrocarbon degradation capacity of Isoptericola peretonis sp. nov. and related species: a comparative study - Vidal-Verdú, Àngela; Latorre-Pérez, Adriel; Pascual, Javier; Mañes-Collado, Ruth; Nevot-Terraes, Aitana; Porcar, Manuel (Frontiers in Microbiology, 2025)
Since the beginning of their production and use, fossil fuels have affected ecosystems, causing significant damage to their biodiversity. Bacterial bioremediation can provide solutions to this environmental problem. In this study, the new species Isoptericola peretonis sp. nov. 4D.3T has been characterized and compared to other closely related species in terms of hydrocarbon degradation and biosurfactant production by in vitro and in silico analyses. Biosurfactants play an important role in microbial hydrocarbon degradation by emulsifying hydrocarbons and making them accessible to the microbial degradation machinery. The tests performed showed positive results to a greater or lesser degree for all strains. In the synthesis of biosurfactants, all the strains tested showed biosurfactant activity in three complementary assays (CTAB, hemolysis and E24%) and rhamnolipid synthesis genes have been predicted in silico in the majority of Isoptericola strains. Regarding hydrocarbon degradation, all the Isoptericola strains analyzed presented putative genes responsible for the aerobic and anaerobic degradation of aromatic and alkane hydrocarbons. Overall, our results highlight the metabolic diversity and the biochemical robustness of the Isoptericola genus which is proposed to be of interest in the field of hydrocarbon bioremediation.